Generación del mapa geomorfológico a escala 1:25000, de las parroquias rurales San Pedro de la Bendita, Zambi y Guayquichuma, correspondiente a la parte norte del cantón Catamayo, provincia de Loja, Ecuador. - Abad Chiriboga, Eduardo Alfredo (2021)
Currently, most entities use geographic information systems focused on the generation of digital cartography, which is why this research project was developed under the title of "Generation of the Geomorphological Map at 1:25000 scale, of the rural parishes of San Pedro de la Bendita, Zambi and Guayquichuma, corresponding to the northern part of the canton Catamayo, province of Loja, Ecuador", The same one that comprises the quantitative characterization of the relief using the method of automatic classification isodata, applied to the Digital Elevation Model (DEM) in the ENVI 5.3 software. In addition to the aforementioned procedure, it was perfected with 3D observation and landscape interpretation by means of field trips; as a result, 9 geoforms of mesorelief and 5 with respect to macrorelief were obtained, of which 4 genetic classes have been defined. Complemented the research work with the generation of the landslide susceptibility map of the study area.